2018
DOI: 10.1002/joc.5564
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability in Iran in response to the diversity of the El Niño‐Southern Oscillation

Abstract: Through emitting large-scale planetary waves, the El Niño-Southern Oscillation (ENSO) contributes to the inter-annual climate variability in extra-tropical latitudes, although the impact may be intervened by the chaotic extra-tropical atmosphere. Using meteorological records of 45 synoptic stations across Iran during the period 1980-2016, impacts of La Niña and the eastern Pacific (EP) and central Pacific (CP) El Niño events on the inter-annual climate variability of Iran are investigated. The data for four EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…The impacts of ENSO on the climate of Iran have been fully discussed by Alizadeh‐Choobari et al . () and Alizadeh‐Choobari and Najafi (). It can be observed that large errors in the simulated 2‐m temperatures (both in RegCM4 and the driving CSIRO‐Mk3.6) are associated with one of the contrasting phases of ENSO.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The impacts of ENSO on the climate of Iran have been fully discussed by Alizadeh‐Choobari et al . () and Alizadeh‐Choobari and Najafi (). It can be observed that large errors in the simulated 2‐m temperatures (both in RegCM4 and the driving CSIRO‐Mk3.6) are associated with one of the contrasting phases of ENSO.…”
Section: Resultscontrasting
confidence: 99%
“…As ENSO is the main process that contributes to interannual climate variability in many regions of the globe (McPhaden et al, ; Alizadeh‐Choobari, ), including Iran (Alizadeh‐Choobari et al, ; Alizadeh‐Choobari and Najafi, ), quality of seasonal climate forecasting also strongly depends on the skill of the driving GCM in prediction of ENSO (Doblas‐Reyes et al, ). A better inclusion of processes that lead to ENSO events and teleconnections associated with them in driving GCMs will certainly improve seasonal climate forecasting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change, encroaching on floodplains, land use changes, diversion of the waterways, destructive effects of human activities, degradation of forests and pastures, and the construction of dysfunctional and vulnerable hydraulic structures can be mentioned as the reasons for increasing flood risks (Wang et al, 2019;Tang, 2020). The magnitude and frequency of flood events in each region depends on several factors: (i) physiographical features of the catchment such as shape, slope, and river network density, (ii) hydrological features such as precipitation, storage and initial losses, evapotranspiration, and permeability, (iii) human activities, (iv) large-scale atmospheric signals, and (v) climate change (Noori et al, 2011;Ward et al, 2014a, b;Alizadeh-Choobari and Najafi, 2017;Hooshyaripor and Yazdi, 2017;Hooshyaripor et al, 2017;Saghafian et al, 2017;Hao et al, 2018). These factors affect the frequency and intensity of floods and consequently the amount of damage costs.…”
Section: Introductionmentioning
confidence: 99%